Using Participatory Process Evaluation to Understand the Dynamics of C hange in a Nutrition Education Programme - Cornwall, Andrea (IDS Working Papers, 2014)
With roots in approaches to popular education and participatory action research that place the learner and the ‘beneficiary’ of development at the centre of enquiry and action, the participatory visualisation m ethods associated with Participatory Rural Appraisal have been widely used as tools for learning and accountability. In this article, I refl ect on lessons learnt from using these methods in a participatory proc ess evaluation of an educational programme aimed at addressing chronic malnutrition in an East African country. Building on this experience, I explore the educative and empowering dimensions of participatory vi sualisation methods, and consider the contribution that these methods can make to effective evaluation.
Keywords: Kenya; nutrition; participatory impact evaluation; process evaluation; randomised controlled trials